Expansive assessment of expansive abilities: Teachers’ perspectives and practices with multimodal and translanguaged content assessments - Grapin, Scott E.; Ascenzi-Moreno, Laura (Learning and instruction, 2024)
Expansive assessment seeks to reimagine assessment in content and language integrated learning (CLIL) through the lens of expansive theories of communication (e.g., multimodality, translanguaging). However, for expansive assessment to be consequential for students in CLIL classrooms, teachers must be open to recognizing student learning expressed in ways that go beyond what has been traditionally privileged (e.g., written English). This article reports on two complementary studies of U.S. teachers’ perspectives and practices related to expansive assessment. Study 1 addressed multimodal assessment with pre-service teachers (PSTs) in science. Study 2 addressed translanguaged assessment with in-service teachers (ISTs) in language arts. Participants in Study 1 were 10 PSTs. Participants in Study 2 were two ISTs from different elementary schools with different instructional arrangements. Interviews and observations were used to elicit teachers' perspectives on expansive assessment and their practices interpreting students’ performances. In both studies, teachers' perspectives closely reflected their practices. For example, PSTs whose perspectives eschewed logocentrism tended to recognize evidence of science learning in students' visual responses. However, there were also findings unique to each study. For example, ISTs’ perspectives and practices related to translanguaged assessment were mediated by the language policies at their schools. The two studies, which examined different teacher populations, assessment approaches, and content areas, converge in highlighting three overarching themes to guide future research: (a) the importance of clarity regarding constructs assessed, (b) the contextual mediation of teachers’ perspectives and practices, and (c) the need for teacher learning across their careers. •Expansive assessment can offer a more complete picture of students' content learning.•Teachers' perspectives on expansive assessment reflect their assessment practices.•Teachers' perspectives and practices are mediated by their contexts.•Teachers may benefit from critical reflection on their perspectives and practices.